Clinical outcome following duraplasty in type 1 Arnold Chiari malformation - Bettaswamy, Guruprasad; Raykar, Rajesh R.; Singh, Rajesh Kumar; M., Mahendra (International Surgery Journal, 2019)
Background: Few authors support the use of duraplasty and few authors have reported a higher rate of complications associated with the same. The objective of the present endeavor was to study clinical outcome following duraplasty in type 1 Arnold Chiari malformation. Methods: Retrospectively, 24 cases and prospectively 18 cases diagnosed and operated for Chiari malformation type I were included. Patients with Chiari type II, III, and IV were excluded. A questionnaire was used to assess the improvement in neck pain and disability due to it, head pain and disability due to it and improvement in general health before and one year after surgery. The results of the questionnaire of both groups were analyzed and compared. Results: The most common age group of presentation was 2nd decade (35.71%) followed by 3rd decade (26.19%). The male to female ratio was 1.2:1. The most common presenting complaint was sensory disturbances (66.66%) followed by neck pain in 14 patients (33.33%). The most common sign was limb weakness in 21 patients (50%). 24 patients were operated with foramen magnum decompression with duraplasty and 18 patients were operated without duraplasty. There were more complications in the duraplasty group. Patients showed an overall clinical improvement of 83.33% in the duraplasty group compared to a lower overall clinical improvement rate of 55.50% in the no duraplasty group. Specific symptoms like neck pain showed similar rate of improvement of (88.89%) in the duraplasty group compared to no duraplasty group (80%). Conclusions: Foramen magnum decompression with duraplasty is superior to foramen magnum decompression without duraplasty although slightly higher rate of complication is seen with duraplasty.